Perubahan tingkat kekerasan ereksi pada pasien BPH paska pemberian α1A- adrenoreceptors antagonis di RSUP H. Adam Malik Medan - Muhammad Eka Agusfansyah; Syah Mirsya Warli; Bungaran Sihombing (Majalah Kedokteran Nusantara The Journal Of Medical School, 2012)
Background : Lower urinary tract infection (LUTS) at benign prostate hyperplasia (BPH) patient commonly followed by sexual dysfunction which include erectile dysfunction, at last study there was relation between LUTS/BPH and erectile dysfunction.1a-adrenoceptors antagonists (Tamsulosin) is very selective adrenoceptor •1 antagonist. These drugs block a adrenaceptor1a the prostate which further led to improvement of LUTS symptoms and also blocked the action of noradrenaline at the level1a receptors on smooth muscle of the corpus cavernosum to enhance and improve erectile function. The purpose of this study was to determine changes in the level of erection hardness in patients with BPH after administration •1a-adrenoceptors antagonists for 1 month.Methods : This research is an experimental study. Anamnesis directly performed on 50 subjects who met the inclusion criteria and did not meet the exclusion criteria. To assess the degree of erection hardness using a special instrument that used erection hardness score (EHS), where EHS is a diagram of the quality of erection hardness which consisted of grade 1 to 4. Patients will be assessed level of erection hardness using EHS before and after the intervention for 1 month with •1a-adrenoceptors antagonistsResult : Based on statistical analysis, after administration of •1a-adrenoceptors antagonists found there was a significant increase in the value of EHS compared with before intervention, with P value = 0.001 (• = 0.005 CI = 95%). 36 subjects with EHS 2 before intervention, 16 subjects turned into EHS 3 after the intervention. 13 subjects with EHS 3 before the intervention, after the intervention did not change the value of EHS. One subject with EHS 4 before intervention also did not change after the intervention.Conclusion : This study proved that •1a-adrenoceptors antagonists can improve erectile dysfunction in patients with BPH. Keywords : BPH; erectile dysfunction; •1a-adrenoceptors antagonists; LUTS; EHS